2013
DOI: 10.1097/acm.0b013e31827c562d
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Ultrasound Training for Fourth-Year Medical Students

Abstract: Ultrasound training and education in medical schools is rare, and the foci of current ultrasound curricula are limited. There is a significant need for advanced ultrasound training models in medical school curricula to reduce educational burdens for physician residency programs and improve overall physician competency.The authors describe and evaluate the advanced ultrasound training program developed at The Ohio State University College of Medicine (OSU COM). The OSU COM program is a longitudinal advanced ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Several studies have shown bedside ultrasonography to be a feasible addition to medical school education with a handful of schools reporting successful integration of a vertical curriculum over four years 4,11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown bedside ultrasonography to be a feasible addition to medical school education with a handful of schools reporting successful integration of a vertical curriculum over four years 4,11…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts have been well received by students who report a high level of satisfaction with ultrasonography as well as interest in additional training and incorporation of bedside US during medical school education. Efforts have also shown that POCUS introduced during anatomy and the physical exam course show promise to increase students’ knowledge 416…”
Section: Introductionmentioning
confidence: 99%
“…Although medical students can reach national sonographer standards with a structured integrated approach [5], the majority of student scores tended to be akin to 'a borderline level of competency'. This underscores the need for a structured approach to undergraduate ultrasound education which incorporates a robust image review and management system [15]. Many programs up to this point have been evaluated using various pre-and post-test questionnaires, MCQ exams and checklists; however, validated tools are emerging [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Some [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Fifteen papers describe variously integrated ultrasound curricula. Five studies are notable for the numbers of medical students involved in a formal evaluative process (>150) [5][6][7][8][9].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Because of these new competencies and an increased use and availability of ultrasound technology in many medical disciplines, there is a great need to train a new generation of physicians that are capable and confident with ultrasound. A few medical schools have now integrated ultrasound into all four years of their medical training [13], enabling their students to be leaders and teachers of ultrasound in both their clerkships and residencies [14–16]. These institutions have reported that many kinds of formal ultrasound training significantly increase competency in ultrasound fundamentals for both medical students [13–15] and residents [17].…”
Section: Introductionmentioning
confidence: 99%